Crystal structure of poly[aqua-(μ 2-3-bromoisonicotinato-κ 2 N: O)-(μ 2-3-bromoisonicotinato-κ 3 N: O: O′)-(μ 3-3-bromoisonicotinato-κ 3 N: O: O′)-(μ 2-nitrite-κ 3 O: O′: O″)dicadmium(II) monohydrate], C19H12Br3Cd2N3O9 - Li Kuan-Ying; Wang Yue; Zheng Qing-Hua; Zhou Wei-Wei (Zeitschrift für Kristallographie - New Crystal Structures)
C19H12Br3Cd2N3O9, triclinic, P 1− $\overset{-}{1}$ (no. 2), a = 8.5783(3) Å, b = 10.1346(3) Å, c = 15.5520(5) Å, α = 85.633(1)∘, β = 89.906(1)∘, γ = 65.269(1)∘, V = 1223.80(7) Å3, Z = 2, R gt(F) = 0.0368, wR ref(F 2) = 0.0935, T = 299 K.